THE WOMEN WHO LIVE IN CĂTĂLINA FLORINA FLORESCU’S CORP DE TEATRU ÎN CINCI ROCHII STRĂLUCITOARE (THEATER BODY IN FIVE SHINING GOWNS) - Diana Alexandra AVRAM (ȘANDRU) (Incursiuni în imaginar)
Cătălina Florina Florescu, a Romanian scholar and professor at Pace University in New York, publishes her second volume of plays in Romanian in 2024, further establishing her presence as a diasporic writer in her native country. Continuously engaged with how the major themes of humanity and literature are reflected in Romanian society, Cătălina Florescu persists in writing in her mother tongue and seeking connections with the Romanian audience beyond geographical boundaries. Corp de Teatru (În Cinci Rochii Strălucitoare) [Theatre Body (In five shining gowns)] is yet another significant addition to the contemporary Romanian theatrical scene, featuring plays that have been nominated for and awarded in the field.